MODELO DE INTERVENCIÓN PARA LA PROTECCIÓN DE INVENCIONES EN INSTITUCIONES DE EDUCACIÓN SUPERIOR MEXICANAS - López, Marco Tulio Cerón; Moreno, Francisco Javier León; Flores, Verónica; Pérez, Manuel González (European Scientific Journal, ESJ, 2015)
The patent is the means of protecting an invention; you can get the inventor and gives exclusive right to the use thereof. Institutions of higher education are the main sources of research, innovation and technological development in Mexico, who must develop strategies or made or proposed to support the generation and protection of inventions arising within institutions. The Intervention Model for the Protection of Inventions in Mexican Higher Education Institutions (MIPI in AIMS) is a proposal that aim to create a culture of industrial protection of inventions arising within Higher Education Institutions (HEIs), which meet the requirements established by the Industrial Property Law (LPI) and the Mexican Institute of Industrial Property (IMPI).